In Vitro Activities of Six Quinolones and Mechanisms of Resistance in Staphylococcus aureus and Coagulase-Negative Staphylococci - Linde, Hans-Jörg (American Society for Microbiology, 2001)
Of 94 clinical isolates of Staphylococcus aureus (n = 51) and coagulase-negative staphylococci (CNS) (n = 43), mutations in the quinolone resistance-determining region of topoisomerases GrlA, GrlB, GyrA, and GyrB together with MICs of six quinolones were analyzed. Amino acid substitutions at identical residues (GrlA residues 80 and 84; GyrA residues 84 and 88) were found in S. aureus and CNS. Active efflux, as suggested by blocking by reserpine, contributed substantially to the resistance phenotype in some strains. Among ciprofloxacin, clinafloxacin, levofloxacin, nalidixic acid, trovafloxacin, and sparfloxacin, a 0.5-μg/ml concentration of sparfloxacin discriminated best between strains with two or three mutations and those with no mutations.